2020
DOI: 10.1177/1368430220920717
|View full text |Cite
|
Sign up to set email alerts
|

Sociopsychological correlates of militant extremist beliefs in a postconflict society: The importance of ethnocentrism and quality of interethnic contacts

Abstract: This study investigates the attitudinal and motivational bases of militant extremist beliefs in a postconflict society ( N = 600; 51% female). Militant extremist mindset (MEM) measures of proviolence, divine power, utopianism, vile world, and West, together with the Ethos of Conflict- Grudge Scale (EOC-grudge), were used to assess militant-extremist beliefs. Data about the socioeconomic status (SES) of participants, ethnocentrism, intergroup contact, trust in the system, and the level of conflict in the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Post-conflict society in this region appears to be characterized by a high level of Grudge, resentment, and bitterness. Some contextual and social mechanisms that facilitate such political radicalization have been detected and discussed in our previous work (Stankov et al, 2020). This facilitation, as our present findings show, is especially likely in those individuals (and certain social groups, such as football supporters and various right-wing oriented groups, Međedović et al, 2020) prone to develop a closed system of beliefs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Post-conflict society in this region appears to be characterized by a high level of Grudge, resentment, and bitterness. Some contextual and social mechanisms that facilitate such political radicalization have been detected and discussed in our previous work (Stankov et al, 2020). This facilitation, as our present findings show, is especially likely in those individuals (and certain social groups, such as football supporters and various right-wing oriented groups, Međedović et al, 2020) prone to develop a closed system of beliefs.…”
Section: Discussionsupporting
confidence: 75%
“…All materials, data, and code are available at https://osf.io/nea73/. The same sample was used in two publications: Stankov et al (2019) and Stankov et al (2020). This study explores a different research question and the present analyses have not been reported before.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Stankov et al (2020) tested and supported the hypotheses that extremist beliefs are associated with a high level of ethnocentrism, low socioeconomic status, decreased intergroup contact, low trust in the system, and recent intergroup conflict.…”
Section: The Militant Extremist Mindsetmentioning
confidence: 97%